Perilipin 2 and Age-Related Metabolic Diseases: A New Perspective. (December 2016) - Conte, Maria; Franceschi, Claudio; Sandri, Marco; Salvioli, Stefano
Abstract : Perilipin 2 (Plin2), a protein associated with the metabolism of intracellular lipid droplets (LDs), has long been considered only for its role in lipid storage. However, the manipulation of its expression affects the severity of a variety of metabolic and age-related diseases, such as fatty liver, insulin resistance and type 2 diabetes (T2D), cardiovascular disease, atherosclerosis, sarcopenia, and cancer, suggesting that this protein may play a role in these pathological conditions. In particular, its downregulation in mice prevents or mitigates some of the above mentioned diseases. Conversely, in humans high levels of Plin2 are present in sarcopenia, hepatic steatosis, atherosclerosis, and some types of cancer. We propose that inhibition of Plin2 might be a strategy to counteract several metabolic and age-related diseases. Trends: Perilipin 2 (Plin2) is linked to lipid deposition in nonadipose tissues and its increased expression is associated with various metabolic diseases (insulin resistance, type 2 diabetes, atherosclerosis, and cardiovascular diseases) in both animals and humans, with the notable exception of endurance athletes. Downregulation of Plin2 in vivo protects animal models against experimentally induced metabolic diseases, suggesting a broader role for Plin2 beyond lipid storage. Plin2 expression appears to also be associated with pathological conditions such as sarcopenia and cancer, both age-related diseases. Experimental data suggest that, at least in non-alcoholic fatty liver disease, a possible link between Plin2 and liver steatosis could be inflammation. It is possible, but not yet demonstrated, that this link also exists for other pathologies that have been associated with increased Plin2 expression.